Method for preparing taxane derivatives - Pyo, Sang-Hyun; Cho, Jin-Suk; Kim, Moon‐Suk; Song, Jai-Young; Choi, Ho-Joon (United States Patent and Trademark Office, 2012)
Provided is a method for preparing a taxane derivative, comprising: carrying out condensation of a phenylisoserine derivatives having a protective group introduced thereto or a mixture of isomers thereof, as a side chain, with a baccatin III derivative or 10-deacetyl-baccatin III derivative to obtain a mixture of isomers; separating the isomers via chromatography; and carrying out a reversion of the stereochemical structure of a selectively separated isomer, which is suitable for producing a taxane derivative in a large scale with high yield.